Profile of european proton and carbon ion therapy centers assessed by the EORTC facility questionnaire - Weber, Damien; Herfarth, Klaus; Debus, Jürgen (Radiotherapy and oncology, 2017)
Background - We performed a survey using the modified EORTC Facility questionnaire (pFQ) to evaluate the human, technical and organizational resources of particle centers in Europe. - Material and methods - The modified pFQ consisted of 235 questions distributed in 11 sections accessible on line on an EORTC server. Fifteen centers from 8 countries completed the pFQ between May 2015 and December 2015. - Results - The average number of patients treated per year and per particle center was 221 (range, 40-557). The majority (66.7%) of centers had pencil beam or raster scanning capability. Four (27%) centers were dedicated to eye treatment only. An increase in the patients-health professional FTE ratio was observed for eye tumor only centers when compared to other centers. All centers treated routinely chordomas/chondrosarcomas, brain tumors and sarcomas but rarely breast cancer. The majority of centers treated pediatric cases with particles. Only a minority of the queried institutions treated non-static targets. - Conclusions - As the number of particle centers coming online will increase, the experience with this treatment modality will rise in Europe. Children can currently be treated in these facilities in a majority of cases. The majority of these centers provide state of the art particle beam therapy.